Petroleum production engineering : petroleum production economics - Uren, Lester Charles (New York ; London : McGraw-Hill book company, inc., 1950)
This book has for its objective, an elementary exposition of the principal divisions of economics and business administration and their applications to the specific problems of the petroleum and natural-gas industries.
Includes bibliographical references and index.
ne 21/01/2019
Loans
Keywords: Petroleum engineering